Pulmonary Hypertension Associated with Left Heart Disease - Adir, Yochai; Amir, Offer (Seminars in Respiratory and Critical Care Medicine, 2013)
Left heart disease (LHD) is probably the most frequent cause of pulmonary hypertension (PH). Although rheumatic mitral valve stenosis has been in the past the most common cause of this condition, PH-LHD mainly results from heart failure related to systolic and/or diastolic dysfunction of the left ventricle and is associated with elevated left-sided cardiac filling pressures. Most patients have passive increase in pulmonary arterial pressure because of backward transmission of the elevated left atrial pressure, whereas a small subset develop severe PH with elevated transpulmonary gradient and pulmonary vascular resistance. When present, PH is usually associated with a poor prognosis and increased mortality. Optimizing heart failure regimens and corrective valve surgery are the cornerstones of the treatment of PH in LHD. Although PH-LHD may evolve to right ventricular failure and is associated with some changes in the pulmonary vascular bed similar to pulmonary arterial hypertension (PAH), there is no evidence-based data to support the use of PAH-specific therapies in the setting of PH-LHD. However, recent studies suggest the usefulness of sildenafil, a phosphodiesterase-5 inhibitor. This review addresses the epidemiology, pathophysiology, risk factors, and treatment controversies of PH due to LHDs.
Keywords: heart failure; left heart disease; pulmonary hypertension; valvular disease